1996
DOI: 10.1111/j.1440-1754.1996.tb02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Definition of neonatal hypoglycaemia: Is there a change?

Abstract: From 1986 to 1992 there was a significant change in the definition of hypoglycaemia both among paediatricians and in neonatal textbooks compared with the definition in use during 1965-88. The findings suggest that neonatal paediatricians do change in their practice. The changes in the definition of hypoglycaemia may be due to the data available and discussion on hypoglycaemia since 1988. Neonatal paediatricians still attach significance to clinical signs associated with hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…There is no consensus regarding the definition of neonatal hypoglycaemia as many infants at risk (prematurity, small for gestational age, diabetic mother, prolonged labour, perinatal hypoxia or delayed feeding) have very low BGL without clinical signs or symptoms. 6,7 In recent surveys of Australian 8 and UK neonatologists, 9 their responses indicated a BGL of less than 1 to less than 4 mmol/L. However, the majority indicated that they would carry out therapeutic intervention if BGL was less than 2 mmol/L in term infants.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus regarding the definition of neonatal hypoglycaemia as many infants at risk (prematurity, small for gestational age, diabetic mother, prolonged labour, perinatal hypoxia or delayed feeding) have very low BGL without clinical signs or symptoms. 6,7 In recent surveys of Australian 8 and UK neonatologists, 9 their responses indicated a BGL of less than 1 to less than 4 mmol/L. However, the majority indicated that they would carry out therapeutic intervention if BGL was less than 2 mmol/L in term infants.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin concentrations were measured in the baseline sample and at the end of the study in all infants. In addition, blood glucose concentrations were measured hourly at the bedside to ensure that normoglycemia (blood glucose Ն40 mg/dL or Ն2.2 mM) was maintained (17)(18)(19). All of the infants included in the g ϩ IL group and in the previously studied (g ϩ AA ϩ IL) [U-13C]glucose and the (g ϩ AA ϩ IL) [2-13C]glycerol groups maintained blood glucose above 2.2 mM on the designed glucose infusion rate [~17 mol/kg/min (3 mg/kg/min)] during the study, whereas in three infants in the g ϩ AA group, the glucose infusion rate was increased by 5.2, 7.9, and 8.3 mol/kg/min (0.9, 1.4, and 1.5 mg/kg/min), respectively, because of blood glucose concentrations that transiently decreased to 36, 36, and 37 mg/dL (2.0, 2.0, and 2.1 mM), respectively.…”
Section: Lipids and Preterm Gluconeogenesismentioning
confidence: 99%
“…outlined the relationship between abnormal evoked potentials and a blood glucose concentration < 47 mg/dL 20 . In addition a change in the definition of neonatal hypoglycemia from 1986 to 1992 has been demonstrated 21,22 . We therefore regarded two consecutive episodes of plasma glucose below 47 mg/dL as the operational threshold criteria.…”
Section: Discussionmentioning
confidence: 99%